Implementation of Border Gateway Protocol (BGP) Community for DDoS Flooding Mitigation in the Communication and Information Agency of East Java Province - Adi Dwi Cahyono; Made Kamisutara (Journal of Social Research, 2025)
Distributed Denial-of-Service (DDoS) attacks are a serious threat to network infrastructure that can cripple services by flooding systems with malicious traffic. This study implements the attributes of the Border Gateway Protocol (BGP) Community together with Remote Triggered Black Hole (RTBH) as an effective mitigation strategy for the Communication and Information Service of East Java Province. The developed solution leverages BGP routing capabilities to quickly identify and discard attack traffic at the network edge through coordinated route marking. Implementation includes the use of BGP Community tags (300:222) to flag dangerous traffic routes, automatic blackhole routing setup through coordination with upstream service providers, and validation of the framework through real-time simulations using GNS3. The results show this solution can mitigate volumetric attacks in seconds, with a 100% blocking rate for marked prefixes while maintaining normal operation for unaffected routes. This approach offers significant improvements in response speed and scalability for government networks facing advanced DDoS threats. The findings of the study provide practical implementation guidance and empirical evidence supporting BGP-based DDoS mitigation, particularly for the Indonesian government's digital infrastructure.